Infant dietary patterns and early childhood caries in a multi-ethnic Asian cohort - Hu, Shijia (2019)
Dental caries, although preventable, remains one of the most prevalent chronic disease worldwide. Most studies focused on the relationship between sugar intake and caries. However, examining multidimensional dietary patterns is becoming increasingly important. Here, we examined the relationship between dietary patterns from ages 6 to 12 months and early childhood caries (ECC) at age 2 to 3-years. Infant dietary data was collected from caregivers and dietary pattern trajectories from 6 to 12 months derived. Oral examinations were carried out by trained calibrated dentists at ages 2 and 3 years. Associations between dietary pattern and ECC were estimated using generalized estimating equation. We found a 3.9 fold lower prevalence of decayed surfaces among children with high Guidelines dietary pattern scores at 6-months (IRR 0.26; CI [0.12–0.53]; p-value < 0.001) and 100% reduction of decayed surfaces with increased intakes of Guidelines dietary pattern foods from 6 to 12-month (IRR 2.4 × 10−4; CI [4.2 × 10−7–0.13]; p-value = 0.01). Suggesting that following the Guideline dietary pattern, which corresponds most closely to current World Health Organization weaning guidelines, at 6 months and an increase in pattern score between 6 and 12 months were protective against ECC development compared to Predominantly breastmilk, Easy-to-prepare foods and Noodles (in soup) and seafood dietary patterns.